Ag18(μ8-S)(p-TBBT)16(PPh3)8: symmetry breaking induced by the core to generate chirality. Issue 18 (5th February 2020) - Tian, Fan; Chen, Rong
Abstract : A novel chiral Ag18 (μ8 -S)( p -TBBT)16 (PPh3 )8 nanocluster with a meso-shell (Ag10 S16 P8 motif) and a crown-like core (SAg8 motif) is reported. Abstract : A chiral silver–sulfur nanocluster with a μ8 -S inside, Ag18 (μ8 -S)( p -TBBT)16 (PPh3 )8, was successfully synthesized and characterized. This nanocluster is composed of a crown-like Ag8 S core and an Ag10 S16 P8 meso-shell. The presence of the core induces symmetry breaking of the nanocluster from S8 to C 4, and therefore endows the cluster with chirality.